Ninoy at Cory magkabiyak na bayani - Landicho, Domingo G. 1939- (Quezon City C & E Publishing, 2010)
The life stories of Senator Benigno S. Aquino Jr. and President Corazon C. Aquino as part of Philippine political history.
In Filipino.
Keywords: Aquino, Benigno S. -- Jr. -- 1932-1983.; Aquino, Corazon Cojuangco -- 1933-2009.; Presidents -- Philippines -- Biography; Philippines -- Politics and government -- 1973-1986.; Philippines -- Politics and government -- 1986-.